OROFACIAL PAIN BECAUSE OF THE TEMPEROMANDIBULAR DISORDERS - husna, amalia (FKG Unlam, 2016)
Background : Temporomandibular disorder (TMD) is a various symptoms that includes the muscles of mastication, the temporomandibular joint (TMJ), and / or surrounding structures are involved. The etiology of TMD is still unknown clearly. This was probably due to occlusion disharmony, psychological stress, trauma and dental treatment. Purpose : To report the case about the patient who was suffering TMD. It was because of the lossing teeth that had been indicated for orthodontic treatment,but the patientÂ was not continuing this treatment. Case : The patient was male, 14 years came with complaints of pain in the joints below the left ear when eating since a month ago and followed trismust since a week ago. Case Management : Clinical examination showed a temporary diagnosis of TMD. The therapy was given oral medication containing antibiotics, anti-inflammatory and muscle relaxant for 5 days. Patients were instructed to eat soft liquid and perform investigations for panoramic images and pictures TMJ (when opening and closing the mouth). The final diagnosis was TMD, so that the patient was referred to the periodonsia and ortodonsia departement to receive the other treatments .